Synthesis, Characterization, and Perfumery Application of Acetal Derivatives of 2-Methyl-3-(4-R-Phenyl) Propanal: A Short Review - Ahmad Mazahar, Mohd Alif Haikal; Jumal, Juliana (Malaysian Journal of Science Health & Technology, 2023)
Perfumes and fragrances are seen as an essential part of life in many countries, and many men and women use perfumes regularly. Originally, the perfume ingredients were derived from natural sources such as essential oils. However, these natural ingredients encountered challenges, such as poor crop quality, a limited supply of supplies, or difficulties using plant or animal extracts. Hence, with the development of synthetic organic chemistry in the 19th century, many ingredients were produced synthetically, resulting from the creativity of laboratory chemists, and used in today’s perfumes. Acetal is one of the synthetic aromatic chemicals used as ingredients in perfume nowadays. This paper review focuses on synthesis and characterization techniques for analyzing acetal derivatives of 2-methyl-3- (4-R-phenyl)propanal and their perfumery application, such as odor characteristics.